Desarrollo un aplicativo web para desplegar los resultados del trabajo investigativo de la Universidad Nacional de Loja denominado “Análisis contable-financiero y de rentabilidad en el proceso de producción de maíz en la Provincia de Loja” - Mocha Brito, Luis Gerardo (2023)
Nowadays, technology has become a priority in most of the activities carried out by the human being. Research is an area where technological activity is present, concidering that ICTs have made the processing and dissemination of information and the results obtained more effective, having a wide range of propagation. The importance of publicizing the results of a research is fundamental in the investigative process, since an information network is created in which it is possible to appreciate, compare, question or reinterpret research results of interest, thus encouraging new studies. Universidad Nacional de Loja is an institution that has different research lines, where each of its departments participate, which are in charge of carrying out investigative work, of which the majority of the results obtained are exposed to a certain public using basic office automation tools (PowerPoint, Excel, etc.), when these results are exposed, they are stored and archived, so they do not have visibility for the general public, which is a disadvantage since they do not have knowledge about the research works done and their results, there may be a delay in other investigative projects or duplication thereof. This type of inconvenience is present at Education, Art and Communication Department, with the research project "Accounting-financial and profitability analysis in the corn production process in the Province of Loja", of which the data exists of research captured on sheets of paper or stored in office tools. Based on this context, in the present Degree Project (DP) a web application was developed where the results of the research project were displayed, taking advantage of the fact that web technology provides access to information from any geographical point. In order to answer the following research question. What is the perceived ease of use of a web application for the for the results of the research work "Accounting-financial and profitability analysis in the corn production process in the Province of Loja"? In this regard, the methodological framework was carried out in two phases, in the first phase the Web application was developed, obtaining the specification of requirements based on the IEEE-830 standard, through the use of the XP methodology and the tools Django, Angular, with the Client-Server architecture to code the web application. Finally, in the second phase, an implementation plan was made for the execution of the product obtained in a controlled environment, based on the ASAP methodology, Sure Step, Oracle Aim, where certain stages were used that fit the TT. In this way, it is concluded that the perceived ease of use of the application was highly positive, thus answering the research question. Keywords: Software development, Web Application, XP Methodology, corn production.